Trio Album for violin, Violoncell and piano - BLOCKX, Jan (The Boston Music, 1916)
Biola dan Cellon1. Serenaden2. Hungarian Dancen3. My Lady Chlon4. Ecstasyn5. Entr'acte-valsen6. Scene Espagnolen7. In the Woodlandn8.Gavotn9. At eveningn10. Romance